2012
DOI: 10.1093/tropej/fms047
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Tamponade due to Fatal Pneumopericardium after Commercial Flight: Transportation of a Premature Infant with Chronic Lung Disease

Abstract: We report a case of cardiac tamponade due to air leak and fatal pneumopericardium that occurred after commercial flight transportation of a premature infant with chronic lung disease without respiratory distress. We review and discuss aspects of flight pathophysiology, and conclude that careful preparation before, and close monitoring during, commercial flight transportation is necessary for premature infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Due to its rare nature, pneumopericardium in children has previously been discussed only in the context of case reports and therefore data on epidemiology are limited. The first description of pneumopericardium appears in an article by Bricheteau in 1844 and isolated cases have been described ever since . Our review is a synthesis of the available evidence and suggests that patients in the first month of life and children undergoing cardiothoracic or abdominal surgery, or with a previous history of hematological disease, and presenting with isolated pneumopericardium are at higher risk of tension pneumopericardium, which presents with a higher mortality compared with patients with other air leak syndromes.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Due to its rare nature, pneumopericardium in children has previously been discussed only in the context of case reports and therefore data on epidemiology are limited. The first description of pneumopericardium appears in an article by Bricheteau in 1844 and isolated cases have been described ever since . Our review is a synthesis of the available evidence and suggests that patients in the first month of life and children undergoing cardiothoracic or abdominal surgery, or with a previous history of hematological disease, and presenting with isolated pneumopericardium are at higher risk of tension pneumopericardium, which presents with a higher mortality compared with patients with other air leak syndromes.…”
Section: Discussionmentioning
confidence: 86%
“…Tension pneumopericardium affects only a minor percentage of patients but results in significant hemodynamic instability . There are very limited data available on nontraumatic pneumopericardium in pediatric patients who are nonventilated …”
Section: Introductionmentioning
confidence: 99%
“…In studies, no relationship between age, gender, tumor type, lymph node metastasis, pleural fluid, dis- 6) reported that cytology of pericardial fluid did not have an effect on the lifetime in non-small cell lung cancer cases that developed tamponade. Video assisted thorascopic surgery (VATS) can only be performed in hemodynamically stable patients because it requires only lung anesthesia (7). When procedure is performed laparoscopically, great caution should be given in the opening of pericardium with cautery.…”
Section: Discussionmentioning
confidence: 99%
“…Serious arrhythmia may develop. Intraabdominal pressure should be lowered when pericardium is opened in order to prevent the development of tamponade (7). It is reported that windows with diameters less than 3 cm, will close quickly, approximately in a year due to adhesion in the liver.…”
Section: Discussionmentioning
confidence: 99%